Kajian Etnomatematika Alat Musik Suling Bali - Pramesti, Angelin Ica (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2022)
Mathematics is a part of a culture that is inherent in all aspects of human life. Ethnomathematics is used to examine certain mathematical practices in certain cultures of society. This study aims to model the placement distance of the pitch control hole on a diatonic Balinese flute with a basic C note to improve the ability to model a mathematical problem. This research uses a descriptive type qualitative research method and ethnographic approach. Using the literature study method and also interviews. Analysis of qualitative research data used is a domain analysis technique. The result of this research is the modeling of the placement of the pitcher hole placement on the diatonic Balinese flute with a basic C note to improve the ability to model a mathematical problem. This research has many shortcomings and has not been carried out in-depth, therefore researchers are advised to dig deeper into knowledge about ethnomathematics on Balinese flute musical instruments both in mathematical aspects such as modeling or other mathematical aspects.